Study of Umbilical Blood Lead Level and Its Relation with Pregnancy Outcome - El Khaleegy, Hany Abdul Hady; Abo baraka, Waleed Ezzat; El-moghazy, Mohammed Khairy (Journal of medical and pharmaceutical sciences, 2019)
Background: Lead exposure continues to be a major health problem that needs more attention in different health disciplines.Objective: to explore the correlation between maternal exposure and cord blood lead levels and to identify potential predictors for umbilical cord blood lead levels and its effect on pregnancy outcome.Methodology: This study is a cross sectional study, which included 100 newborns of healthy pregnant women with singleton pregnancy. The study took place from November 2017 to April 2018. All mothers complete a questionnaire about their demographic data, obstetric history. In addition, their pregnancy outcome was documented and an umbilical cord sample was drawn for determination of lead levels. Patients were divided into two groups according to umbilical cord blood lead levels (high group ≥10 µg/dl) and low group (
Keywords: umbilical cord; lead in the blood carried; new born